The Influence Of Dark Triads As A Personality Factor On Academic Dishonesty Among Students - Siti Qodariah; Milda Yanuvianti; Farida Coralia; Temi Damayanti (Schema: Journal of Psychological Research, 2024)
Abstract. The phenomenon of increasing academic cheating behavior among students raises serious concerns related to academic integrity, legitimate learning, and the quality of graduates, while character education and the development of social values are vigorously echoed in overcoming the challenges of academic honesty in the higher education environment. This study aims to examine the influence of Dark Triads as a personality factor on academic dishonesty among students. The sample of this study involved 115 randomly selected students. The analysis method used is linear regression. The results of regression analysis show that the Dark Triads have a significant and positive influence on academic dishonesty, with an F value of count = 13.630 with a significance level of 0.001 < 0.05, meaning that there is an influence of the Dark Triad on academic dishonesty. The Dark Triad's contribution to academic dishonesty is 11%. Academic dishonesty is still low (77.39%), meaning that there are still many students who are honest. The most abundant aspect of the Dark Triads is Machiavellianism. These findings suggest that the tendency of Dark Triads in college students can increase academic dishonesty behavior. Based on the results of this study, it is recommended that educational institutions strengthen character education programs and academic integrity. Further research is needed to explore other variables that may influence academic dishonesty. Keywords: Academic Dishonesty, Dark Triads